Survey of Dental graduates who have not received Government employment in Sri Lanka - Silva, M.D.K (My University, 1999)
There were 202 dental surgeons belonging to 3 batches of graduates awaiting government appointments by May 1999. Seventy one percent were engaged in private practice.Universities and defence forces were the other main sources of employment. A dental surgeon's monthly income had a median value of Rs.13,800/=.Forty four precent of dental surgeons were concentrated in Colombo district.At present non availability of government employment is not a serious problem as the majority are gainfully employed as private practitioners. In the near future the private sector will be saturated with the passing out of new batches of dental graduates.Therefore non availability of government employment will be a serious problems within next 3 years.Restriction of intake of dental students to the university, introduction of a compulsory internship and provision of incentives to those who wish to establish paractice in rural areas